Determination of Fe Ions Content in Well Water Samples from Dumai Timur Subdistrict of Dumai Municipality - Sari, Yelfira (ALKIMIA, 2020)
One of the raw water sources in Indonesia is well water. However, the water mostly smells, turbit, and dirty. Dumai Timur is one of the subdistricts in the Dumai municipality that have bad quality water. People use well water for daily activities but the water is the smell and the color is yellowish and leaves rust stain in functional partitions. This rust stain estimated as iron ion (Fe2+ and Fe3+). Iron ion needed in red blood cell formation; however, if it exceeds the defined level, this ions is harmful. This research aimed to identify the iron ions level in well water used by people at Kecamatan Dumai Timur. Samples obtained from some well water in Dumai Timur that consist of five Kelurahan. Technique sampling was random sampling and the iron ion was detected in a laboratory using SNI 6989.4:2009. The result compared with the defined level by the Minister for Public Health No. 416/1990.